The half sister [large type] - Jones, Sandie (Thorndike Press large print core, 2021)
"Sisters Kate and Lauren meet for Sunday lunch every week without fail, especially after the loss of their father. But a knock at the door is about to change everything. A young woman by the name of Jess holds a note with the results of a DNA test, claiming to be their half sister. As the fallout starts, it's clear that they are all hiding secrets, and perhaps this family isn't as perfect as it appears" --